Effect of modified Morita therapy combined with motor imagery training on pulmonary rehabilitation of elderly patients with chronic obstructive pulmonary disease (改良森田疗法结合运动想象在老年慢性阻塞性肺疾病患者肺康复中的应用) - ZHOU Chunxiang (周春香); SUN Renjuan (孙仁娟); ZHOU Ru (周茹); TANG Jinghua (唐静华); DING Yexia (丁叶霞); ZHANG Xiaofeng (张晓枫); ZHANG Jianxia (张剑霞) (Association of Integrative Nursing, 2021)
Objective To investigate the effect of modified Morita therapy combined with motor imagery training on pulmonary rehabilitation of elderly patients with chronic obstructive pulmonary disease(COPD). Methods Totally 130 elderly COPD patients were selected and divided into two groups according to the random number table method, with 65 cases in each group. During the rehabilitation treatment, the control group received modified Morita therapy intervention, and the observation group received modified Morita therapy combined with motor imagery training. The changes of lung function, negative emotion and quality of life before and after intervention were compared between the two groups. Results After intervention, the value of forced expiratory volume in 1 s (FEV1), forced expiratory volume in one second/predicted value ratio(FEV1%pred), forced vital capacity (FVC), FEV1/FVC of the observation group were higher than those of the control group (P＜0. 05). Scores of Self-rating Anxiety Scale (SAS), Self-rating Depression Scale(SDS)in the observation group were lower than those in the control group (P＜0. 05). The total score of St George's Respiratory Questionnaire (SGRQ) and dimension scores of symptom, activity and impact in the observation group were lower than those in the control group (P＜0. 05). Conclusion Modified Morita therapy combined with motor imagery training can promote pulmonary function recovery, relieve negative emotion, and improve quality of life in COPD patients. (目的 观察改良森田疗法结合运动想象应用于老年慢性阻塞性肺疾病(COPD)患者肺康复中的效果。方法 选择2019年1月-2020年3月呼吸内科收治的老年COPD患者130例, 按随机数字表法分为对照组和观察组, 各65例。在常规治疗和护理的基础上, 对照组给予改良森田疗法干预, 观察组给予改良森田疗法结合运动想象干预。对比2组干预前后肺功能、不良情绪及生活质量变化情况。结果 干预后观察组第1秒用力呼气容积(FEV1)、第1秒用力呼气容积占预计值百分比(FEV1% pred)、用力肺活量(FVC)、第一秒用力呼气容积与用力肺活量比值(FEV1/FVC)指标均高于对照组(P＜0. 01)。干预后观察组焦虑自评量表(SAS)、抑郁自评量表(SDS)评分均低于对照组(P＜0. 01)。干预后观察组圣乔治呼吸问卷(SGRQ)症状部分、活动部分、疾病影响部分及总分低于对照组(P＜0. 01)。结论 改良森田疗法结合运动想象应用于老年COPD患者肺康复中, 可促进患者肺功能康复, 缓解不良情绪, 提升生活质量。)